Tvoice :um sistema de manipulação de linguagens para auxiliar portadores de necessidades especiais através da web - Gomes, Italo Herbert Santos e (2005)
This work presents the tVoice, software that manipulates tags languages, extracting information and, being integral part of the VoiceProxy system, it aids bearers of special needs in the access to the Web. This system is responsible for the search and treatment of the documents in the Web, extracting the textual information contained in those documents and preceding the capability of generating eventually through translation techniques, an audio script, used by the of interface subsystem of VoiceProxy, the iVoice, in the process of voice synthesis. In this stage the tVoice, besides the treatment of the tag language HTML, processes other two formats of documents, PDF and XHTML. Additionally to allow that, besides the iVoice, other interface subsystems can make use of the tVoice through remote access, we propose distribution systems techniques based in the model Client-Server providers operations of the fashion of a proxy server treatment of documents